Primary alveolar rhabdomyosarcoma of the brain: a case report - Layal Al Mahmasani; Marwan Najjar; Roula Hourany; Abeer Tabbarah; Sara Sinno; Nathalie Chamseddine; Reine Abou Zeidane; Ghid Amhaz; Bassem Youssef; Hazem I. Assi (Journal of Medical Case Reports, 2024)
Abstract Background Primary brain rhabdomyosarcoma is a rare primary brain malignancy with few case reports. The vast majority of cases of primary brain rhabdomyosarcoma occur in pediatric patients, and immunohistochemistry can distinguish it from embryonal subtypes; however, few cases of primary brain rhabdomyosarcoma in adults have been reported in the literature. Case presentation We report the case of a 26-year-old White male patient who was found to have primary brain alveolar rhabdomyosarcoma after developing headaches for several months. A brain MRI revealed a mixed cystic and solid tumor along the vermis of the cerebellum. The patient underwent a gross total surgical resection, which confirmed the diagnosis of alveolar rhabdomyosarcoma. Further staging workup for another primary focus or disseminated disease yielded negative results, confirming the diagnosis of primary alveolar rhabdomyosarcoma of the brain. Conclusion The standard of care for managing this rare type of brain tumor involves surgery with adjuvant chemoradiotherapy. Further studies should be conducted for a better diagnostic and therapeutic understanding.